A Series of Cube-Shaped Polyoxoniobates Encapsulating Octahedral Cu12XmOn Clusters With Hydrolytic Decomposition for Chemical Warfare Agents - Wu, Yan-Lan; Zhang, Rong-Tao; Sun, Yan-Qiong; Li, Xin-Xiong; Zheng, Shou-Tian (Frontiers in Chemistry, 2020)
This study reported a series of cube-shaped polyoxoniobates, {MCu12O8)(Cu12XmOn)(Nb7(OH)O21)8} [M = Nb(1, 2), Ln3+(3), X = I(1, m = 3, n = 3; 2, m = 5, n = 1), Br(3, m = 5, n = 1)]. As the first octahedral Cu12XmOn cluster incorporated polyoxoniobate, the cube-shaped three-shell structure of {MCu12O8)(Cu12XmOn)(Nb7(OH)O21)8} polyanion contains a MCu12O8 body-centered cuboctahedron, a Cu12XmOn octahedron and a {Cu12(Nb7(OH)O21)8} cube. Compounds 1, 2, 3 show effective catalytic activities for the hydrolytic decomposition of chemical warefare agent simulants.